Music therapy and anxiety in Cuban adult patients undergoing tooth extractions. - Chaple Gil, A.M. (2025)
Introduction: Music therapy is a scientific discipline that can influence the decrease of anxiety during medical procedures. Objective: To describe the effects of music therapy on anxiety in Cuban patients undergoing tooth extraction treatment.Material and Methods: A quasi-experimental parallel-group study was conducted. Participants were randomly assigned into two groups (receiving music therapy and not receiving it during tooth extraction treatment). The Cuban version of the Modified Stomatological Treatment Anxiety Scale was used to measure anxiety before and after tooth extraction. Variables such as age, sex, presence of anxiety before and after tooth extraction, and decrease in anxiety were registered. The data were processed in RStudio, applying inferential and Bayesian statistics. Results: In this study, 155 (38.6%) participants were men and 247 (61.4%) were women, for a total of 402 patients. In addition, 93.5% had anxiety before extraction and 73.6% remained anxious after treatment. The odds ratio (1.55) indicates that those who received music therapy have 1.55 times higher odds of experiencing a decrease in anxiety. Bayesian analysis found insufficient evidence to conclude that music therapy reduces anxiety. Conclusions: It cannot be categorically concluded that music therapy decreases anxiety levels during tooth extraction. However, in the group that received music therapy, the majority of participants experienced a percentage reduction in anxiety.